Atmospheric diffuse plasma jet formation from positive-pseudo-streamer and negative pulseless glow discharges - Jing Li (Nature Portfolio, 2021)
Streamer coupling theory is traditionally used to engineer the generation of diffuse plasmas in the regime preceding filamentary discharge, but this method remains inefficient. Here, an alternative route to cost-efficient diffuse plasma generation is proposed, involving the expansion and quenching of existing filamentary discharge.